Targeted inhibition of Gq signaling induces airway relaxation in mouse models of asthma - Matthey, Michaela; Roberts, Richard; Seidinger, Alexander; Simon, Annika; Schröder, Ralf; Kuschak, Markus; Annala, Suvi; König, Gabriele M.; Müller, Christa E.; Hall, Ian P.; Kostenis, Evi; Wenzel, Daniela (American Association for the Advancement of Science, 2017)
Obstructive lung diseases are common causes of disability and death worldwide. A hallmark feature is aberrant activation of Gq protein–dependent signaling cascades. Currently, drugs targeting single G protein (heterotrimeric guanine nucleotide–binding protein)–coupled receptors (GPCRs) are used to reduce airway tone. However, therapeutic efficacy is often limited, because various GPCRs contribute to bronchoconstriction, and chronic exposure to receptor-activating medications results in desensitization. We therefore hypothesized that pharmacological Gq inhibition could serve as a central mechanism to achieve efficient therapeutic bronchorelaxation. We found that the compound FR900359 (FR), a membrane-permeable inhibitor of Gq, was effective in silencing Gq signaling in murine and human airway smooth muscle cells. Moreover, FR both prevented bronchoconstrictor responses and triggered sustained airway relaxation in mouse, pig, and human airway tissue ex vivo. Inhalation of FR in healthy wild-type mice resulted in high local concentrations of the compound in the lungs and prevented airway constriction without acute effects on blood pressure and heart rate. FR administration also protected against airway hyperreactivity in murine models of allergen sensitization using ovalbumin and house dust mite as allergens. Our findings establish FR as a selective Gq inhibitor when applied locally to the airways of mice in vivo and suggest that pharmacological blockade of Gq proteins may be a useful therapeutic strategy to achieve bronchorelaxation in asthmatic lung disease.